Steady-State Operation, Disturbed Operation and Protection of Power Networks - Vallée, François (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents the latest state-of-the-art research on solid fuels technology with dedicated, focused research papers. There are a variety of topics to choose from among the seven published re-search works to bring you up to date with the current trends in academia and industry.